Establishment of absorbed doses in fabricated Ge-doped optical fibres for breast radiotherapy dosimetry - Zakaria, Z.; Ng, A. H.; Bradley, D. A.; Mohd Noor, N. (Elsevier Ltd, 2025)
In this work, the calculated and measured mean absorbed doses in breast dosimetry are performed for breast tumour volumes and skin doses. The measurements are made use of Fabricated Ge-Doped Optical Fibres (FGDOF) with comparison with Treatment Planning System (TPS), Lithium Fluoride (LiF) chips and Gafchromic™ (EBT3 films). Two FGDOF shapes (cylindrical and flat) and different germanium (Ge) dopant (2.3 mol% and 6.0 mol%) are used. The TPS parameters used for both breast tumours and skin doses were SSD of 100 cm, 10 MeV electron energy and dose of 2 Gy where the small breast tumour with 10 cm × 10 cm and the large breast tumour with 14 cm × 14 cm. The result showed the mean absorbed dose of FGDOF showed an insignificant difference at p > 0.05 for skin doses, small tumour volume and large tumour volume measurement when compared to the calculated dose obtained from the TPS. In conclusion, the developed FGDOF, particularly flat fibre, is found to be suitable for breast dosimetry.